KARAKTER VISUAL KAWASAN KOTABARU, YOGYAKARTA BERDASARKAN KONSEP GARDEN CITY - , Yunita Kesuma, S.T ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Kotabaru which is one of the Dutch colonial settlement areas in Yogyakarta, applying concepts developed as Garden City or Tuinstaad, and has been set as the heritage area. As a Dutch colonial settlement expansion efforts (new town in town) in Yogyakarta, Kotabaru (Nieuwe Wijk) in the early planning stages, was built various support facilities as a basic social amenities for the European group. Pressures of economic activity and the process of modernization in Kotabaru be one of preservation related issues in maintaining the visual character Kotabaru it has its trademark. The aim of this research is to identify the determinants of the visual character of Kotabaru as the Dutch colonial heritage based on the Garden City principles and determines the guidelines as the basis for development of the area in terms of preservation of the visual character in Kotabaru. Visual character of the area is determined by the physical elements forming the street space. The method used in this research is qualitative descriptive method. Research emphasis on the observations forming elements of visual character in Kotabaru, such as solid urban elements (buildings mass and vegetation) and elements urban voids (green open space and street space), which affect the display of physical elements in the street space. Based on the results of the discussion, it was concluded that visual character of Kotabaru is the main impression of the physical elements performance that was captured by observers when he moves on the pathway of Kotabaru area as the Dutch colonial heritage. The determinants of the visual character in Kotabaru, in terms of the Garden City principle are: Physical potential of Kotabaru land